2021
DOI: 10.1002/jobm.202100363
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of microalgae in heavy metal bioremediation

Abstract: Microalgae have been publicized for their diversified dominance responsiveness and bioaccumulation potential toward pollutants in an ecosystem. Also, algal's incredible capability as biocatalysts in environmental appliances has been well elucidated owing to their robustness and simple nutritional demand. Additionally, microalgae can deliver various collections of bio-based chemical compounds helpful for diversified applications, especially as green alternatives. The environment has been contaminated with vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…Microalgae have gained attention as suitable candidates for bioremediation, especially for the bio-concentration of heavy metals. As key members of the detoxification mechanism of heavy metal tolerance, ABCs play roles in the uptake, detoxification, and sequestration of heavy metals [ 77 ]. In this study, we found no differently expressed CrABCs under low-Pb stress (3 μM Pb treatment).…”
Section: Resultsmentioning
confidence: 99%
“…Microalgae have gained attention as suitable candidates for bioremediation, especially for the bio-concentration of heavy metals. As key members of the detoxification mechanism of heavy metal tolerance, ABCs play roles in the uptake, detoxification, and sequestration of heavy metals [ 77 ]. In this study, we found no differently expressed CrABCs under low-Pb stress (3 μM Pb treatment).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, at pH 7 when IC of metals vary from 2 mg/L to 10 mg/L, simultaneous elimination of Pb (II), Ni (II), Mn (II), Cd (II) and Cr (VI) changes from 85.29 ± 0.62% to 67.51 ± 0.774%, 85.17 ± 0.64% to 85.44 ± 0.069%, 77.83 ± 0.016% to 77.65 ± 0.429%, 93.2 ± 0.326% to 93.42 ± 0.064% and 75.29 ± 1.367% to 81.37 ± 0.104%, respectively, after same period of incubation. Metals can be accumulated in microalgae up to 10% of their biomass 30 . It is clear that the bioagent (consortium consisting of a cyanobacterium Synechococcus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Metals can be accumulated in microalgae up to 10% of their biomass. 30 It is clear that the bioagent (consortium consisting of a cyanobacterium Synechococcus sp. and green algae Chlorella sp.)…”
Section: Simultaneous Removal Of Heavy Metals and Concentration Of Bi...mentioning
confidence: 99%
“…They adopt approaches, such as extracellular biosorption, bioaccumulation, intracellular compartmentalization, biomethylation, enzymatic reduction, and volatilization to remove harmful metals. 72,73 So, the bottom line is that microalgae could be a key to synthesizing NPs, because they are accessible and easy to produce, their production does not depend on as many factors as plants, and they are less costly, with significantly higher growth and reproduction rates compared to vascular plants, and also microalgae are highly adaptable and can grow in widely varying environmental conditions, including wastewater. 74,75 This broadens the possibilities for cultivation and facilitates the acquisition of biomass, accelerating the process of NPs biosynthesis.…”
Section: Advantages Of the Green Synthesis Of Nps From Microalgae Vs ...mentioning
confidence: 99%